Comprehensive review on anti-obesity effects of plant-derived compounds: Evidence from 3T3-L1 adipocytes and high-fat diet models - Sachin Gudasi; Mrityunjaya B. Patil (Aspects of Molecular Medicine)
Obesity, a multifactorial chronic disease, poses a growing global health concern, contributing to increased incidences of type 2 diabetes, cardiovascular diseases, osteoarthritis, and several cancers. Despite various pharmacological attempts targeting lipid metabolism enzymes, the associated adverse effects have led to numerous drug withdrawals, underscoring the urgent need for safer and more effective therapeutic strategies. In this context, the present study explores the novel therapeutic potential of plant-derived bioactives, specifically formulated using gold nanoparticles (GNPs), for the management of obesity. We systematically investigated the modulation of critical adipogenic and lipogenic regulatory proteins—C/EBP-α, PPAR-α, perilipin-1, adiponectin, FABP4, FAS, and ACC in 3T3-L1 pre-adipocytes and high-fat diet-induced obese mice. Our findings demonstrate that GNP-encapsulated phytoconstituents significantly reduce intracellular lipid accumulation by activating AMPK, a key energy sensor that downregulates pro-adipogenic and lipogenic genes (PPAR-α, C/EBP-α, AP2, SREBP-1c, ACC1, FAS, and LPL), while concurrently upregulating lipolytic and thermogenic genes (HSL, PGC-1α, and SIRT1) and enhancing adiponectin expression. The novelty of this study lies in the synergistic application of nanotechnology and traditional plant-based therapeutics to target obesity at a molecular level, offering a dual advantage of enhanced bioavailability and targeted action. These outcomes provide compelling evidence for the use of functionalized nanoparticles as a next-generation anti-obesity strategy, with potential translational value for clinical application.